1994
DOI: 10.1093/jxb/45.5.597
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cadmium on the behaviour of citric acid in isolated tomato xylem cell walls

Abstract: Effects of cadmium on the sorption of citric acid in isolated xylem cell walls were Investigated. 2.5 nM to 9.5 mM [1.5-14 C]citric acid solutions were perfused through columns of xylem cell wall material, isolated from tomato plants (Lycoperslcon esculentum Mill, cv. Tiny Tim).The anion exchange potential of the column was estimated by amino acid analysis as approximately 46 meq dm" 3 , whereas the apparent anion exchange capacity (A£C) was estimated as 1.65 + 0.18 10 "M (citric acid units). This low AEC was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
9
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 57 publications
6
9
0
Order By: Relevance
“…the same order of magnitude as previously reported fluxes (0.30-2.67 nmol mg −1 dw roots h −1 ) for plants grown in close experimental conditions (Jones and Darrah 1995;Bell et al 2003). Citrate adsorption on roots was significantly higher in presence of Cd, which is consistent with results from Senden et al (1994) who have observed an increase of adsorbed citrate on tomato xylem cell walls when Cd was present in solution. Cadmium was also adsorbed on roots and internalized, with a Cd internalization flux ranging between 0.020 and 0.054 nmol mg −1 dw roots h −1 , which is in the range of previous observed values in similar growing conditions (Hart et al 1998;Berkelaar and Hale 2003).…”
Section: Discussionsupporting
confidence: 90%
“…the same order of magnitude as previously reported fluxes (0.30-2.67 nmol mg −1 dw roots h −1 ) for plants grown in close experimental conditions (Jones and Darrah 1995;Bell et al 2003). Citrate adsorption on roots was significantly higher in presence of Cd, which is consistent with results from Senden et al (1994) who have observed an increase of adsorbed citrate on tomato xylem cell walls when Cd was present in solution. Cadmium was also adsorbed on roots and internalized, with a Cd internalization flux ranging between 0.020 and 0.054 nmol mg −1 dw roots h −1 , which is in the range of previous observed values in similar growing conditions (Hart et al 1998;Berkelaar and Hale 2003).…”
Section: Discussionsupporting
confidence: 90%
“…Obviously, Cd additions resulted in an about 2-fold increase in AEC values for citric acid, for both citric acid concentrations. The order of magnitude of AEC values agrees with values found in experiments with columns of isolated xylem cell walls as reported by Senden et al (1994). The 2-fold increase in response to Cd perfusion corresponds to predictions distilled from earlier column experiments (Senden et al 1994) for 0·05 mM citric acid perfusions.…”
Section: Aecsupporting
confidence: 88%
“…Remarkably, hardly any information exists on the effects of metals on the behaviour of xylem organic solutes. Effects of metals on the behaviour of organic solutes are described and used in various ways in chemistry, most especially in ligand-exchange chromatography (Helfferich 1961(Helfferich , 1962Navratil et al 1975;Davankov & Senechkin 1977;Matejka & Weber 1990;Sud et al 1992), but in plant transport physiology the only information available is reported by Senden et al (1992bSenden et al ( , 1994. In the latter papers, cadmium, calcium and magnesium were shown to affect the sorption of citric acid into columns of isolated tomato xylem cell walls: the total citric acid sorption increased up to 7-fold the control values by metal treatments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, a number of possible ligands i.e., organic acids, amino acids, peptides and proteins, stimulate the root to shoot transport of mineral ions (Callahan et al, 2006). The transport rate of di-or trivalent cations has been reported to be enhanced significantly by complexation with organic acids (Senden et al, 1994;Yang et al, 1997), amino acids, or peptides (Mullins et al, 1986;Senden et al, 1994;Stephan et al, 1996;Clark et al, 1986). Only a small fraction of the metal content in plants is present in the form of free aqua ions.…”
Section: Introductionmentioning
confidence: 99%